Handling Martial Art Groups Conflict through Stakeholder Participation - Zulkarnain, Annas; Prasetyo, Wiyono Eko; Setiawan, Dony; Achmad, Syaefurrahman (Faculty of Law, Universitas Pekalongan, 2024)
Social conflict poses a threat to public security and social order. Between 2018 and 2019, 71 social conflict incidents occurred across Indonesia, including frequent clashes between martial arts group in Jombang Regency. This study aims to analyze a stakeholder participation model for managing such conflicts, focusing on the coordinating role of the Jombang Police (Polres Jombang) and the involvement of multiple stakeholders. A qualitative case study method was applied, with data collected through interviews and document analysis involving police officers, local government officials, educators, martial arts leaders, students, and individuals involved in the clashes. The findings reveal that the collaborative conflict management model in Jombang integrates key components (Forum, Involved Parties, and Activities) with Polres Jombang acting as the main coordinator. This model contributes to outcomes such as enhanced security and public order, social unity, and inter-school cooperation. The study proposes eight strategic solutions to improve the existing collaborative model: developing specific SOPs, strengthening evaluation mechanisms, increasing grassroots participation, mapping institutional capacities, implementing structured action plans, applying interdisciplinary approaches, and promoting cross-sector collaboration. This research contributes to academic and practical discourse by offering a comprehensive model for resolving martial arts-related social conflicts. It also provides a concrete operational framework to reinforce institutional capacity in conflict prevention and resolution.